Aiamie kushkushkutu mishinaigan. - Durocher, Flavien, 1800-1876. (Ka iakonigants, nte opishtikoiats [Quebec] : Nte etat W. Neilson, 1847)
Reproduction of original in: Québec (Québec). Legislature. Attributed to Flavien Durocher--NUC pre-1956 imprints. At head of title: L.J.C. et M.I. Includes some text in Latin. Mode of access: Internet.